Carving Japanese netsuke for beginners - Jubb, Robert (Guild of Master Craftsman, 2011)
Readers can create their own Japanese carvings with this how-to title on the intricate skill of Japanese netsuke. Traditionally created for practical reasons, these fantastic, miniature carvings are now highly collectible works of art. Written in an approachable, personal style with six step-by-step projects to follow and 27 additional ideas each accompanied by colour photographs, this book includes everything readers need to get started.